Aircraft hybrid-electric propulsion: development trends, challenges and opportunities - Andrii Humennyi; Liudmyla Kapitanova; Ruslan Zubar; Valerii Bezkorovainyi; Rufat Jafarov (Авіаційно-космічна техніка та технологія)
Aircraft hybrid-electric propulsion: development trends, challenges and opportunities